2015
DOI: 10.1159/000431320
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of DNA Copy Number Variations by Genomic Single-Nucleotide Polymorphism Array in Fetuses with Congenital Heart Defects

Abstract: Objectives: To evaluate the usefulness of single-nucleotide polymorphism (SNP) array for prenatal genetic diagnosis of congenital heart defect (CHD), we used this approach to detect clinically significant copy number variants (CNVs) in fetuses with CHDs. Methods: A HumanCytoSNP-12 array was used to detect genomic samples obtained from 39 fetuses that exhibited cardiovascular abnormalities on ultrasound and had a normal karyotype. The relationship between CNVs and CHDs was identified by using genotype-phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…EIF2C1 was a central element of the microRNA translational silencing machinery which contributed in hypoxia-inducible factors related pathology such as stroke [24]. Research concentrated on prenatal diagnosis of congenital heart defects revealed that significant copy number variants of RBL2 were detected in fetuses with congenital heart defect [25]. Parallel study indicated that RBL2 in the duplicated region had been linked to heart defects and cardiac development [26].…”
Section: Discussionmentioning
confidence: 99%
“…EIF2C1 was a central element of the microRNA translational silencing machinery which contributed in hypoxia-inducible factors related pathology such as stroke [24]. Research concentrated on prenatal diagnosis of congenital heart defects revealed that significant copy number variants of RBL2 were detected in fetuses with congenital heart defect [25]. Parallel study indicated that RBL2 in the duplicated region had been linked to heart defects and cardiac development [26].…”
Section: Discussionmentioning
confidence: 99%
“…RPGRIP1L has been reported to play a critical role in ventricular wall and septum formation (Gerhardt, Lier, Kuschel, & Ruther, ). A deletion overlapping RBL2 has been reported in an infant with atrioventricular septal defect (Tang et al, ). NKD1 has been shown to be a passive inhibitor of the Wnt signaling pathway and SALL1 functions as transcriptional activator of the Wnt signaling pathway (Angonin & Van Raay, ; Morita et al, ; Sato et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Retinoblastoma‐like 2 ( RBL2 ) is a key regulator of entry of a cell into cell division. RBL2 maintains the overall chromatin structure in a cell, particularly the structure of constitutive heterochromatin, which is stabilized by histone methylation and deletions in this region have been associated with CHD (Tang et al, ). SALL1 has been reported to act as a regulator of cardiac progenitor cells defining their fate (Morita et al, ).…”
Section: Discussionmentioning
confidence: 99%